2022
DOI: 10.1002/jso.27113
|View full text |Cite
|
Sign up to set email alerts
|

The impact of race/ethnicity on pancreaticoduodenectomy outcomes for pancreatic cancer

Abstract: Purpose: To investigate the impact of race/ethnicity on surgical outcomes following pancreaticoduodenectomy for pancreatic cancer. Methods: A retrospective review of patients undergoing pancreaticoduodenectomy for adenocarcinoma in the National Surgical Quality Improvement Program (NSQIP) database from 2014 to 2019. Patient and tumor characteristics and 30-day postoperative outcomes were compared. Multivariable logistic and linear regression models were conducted to investigate the relationship between race/et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Interestingly, we found that Asian race was associated with greater rates of CR-POPF, while Black race was linked to reduced risk. The mechanisms underlying this finding are unclear but likely related to variations in access to care, foregut anatomy, and utilization of neoadjuvant therapy 28,29 . Further study is necessary to understand drivers of this relationship and to ensure that inclusion of race in this ML model does not perpetuate health care disparities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that Asian race was associated with greater rates of CR-POPF, while Black race was linked to reduced risk. The mechanisms underlying this finding are unclear but likely related to variations in access to care, foregut anatomy, and utilization of neoadjuvant therapy 28,29 . Further study is necessary to understand drivers of this relationship and to ensure that inclusion of race in this ML model does not perpetuate health care disparities.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying this finding are unclear but likely related to variations in access to care, foregut anatomy, and utilization of neoadjuvant therapy. 28,29 Further study is necessary to understand drivers of this relationship and to ensure that inclusion of race in this ML model does not perpetuate health care disparities. Nonetheless, while information about the tangible impact of each risk factor on CR-POPF is important in managing the postoperative course, it is equally critical to deploy targeted mitigation strategies based on the risk profile of each patient.…”
Section: Discussionmentioning
confidence: 99%